Finding stability between sports ministry and sports ministry management. A church-based review. - Jimmy Smith (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2022)
The field of sports has multiple segments including youth, recreational, college, and professional sport. Research in these areas have produced an abundance of inquiries discussing several managerial function and capacity topics such as finance, marketing, organizational effectiveness, and leadership. While these topics have been applied to many segments of the sport world, the niche segment of sports ministry has not seen these applications. Sports ministers have challenges in that they manage all aspects of the sports programs they provide to the community, but they also supply the resources and support toward the ministry within these programs. The current research fills a gap in existing literature by enhancing the understanding of several managerial functions and capacities of sports ministry managers. In-depth semi-structured interviews were conducted with 21 sports ministers throughout the United States to gain perspectives on their managerial duties with their sports ministry programs. Results and implications for sports ministers indicated that strengths were found in leadership philosophies and evaluating programming, however, role difficulties were clear in planning, managing volunteers, lack of support from upper administration and the feeling of burnout due to poor financial and human resources.
Keywords: Sport management; sport ministry; sports outreach